2018
DOI: 10.1016/j.tranon.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Platinum Sensitive and Resistant Epithelial Ovarian Cancer Patient Samples Reveals New Candidates for Targeted Therapies

Abstract: Ovarian cancer has the highest mortality rate of all gynecologic malignancies. Identification of new biomarkers is highly needed due to its late diagnosis and high recurrence rate. The objective of this study was to identify mechanisms of therapy resistance and potential biomarkers by analyzing mRNA and protein expression from samples derived from patients with platinum-sensitive and -resistant ovarian cancer (total cohort n = 53). The data revealed new candidates for targeted therapies, such as GREB1 and ROR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…Here, we tested the effect of the glucocorticoid DEX on ROR1 signaling activation and analyzed the global changes in drug responses in OC preclinical models, including platinum-resistant cells. We developed cisplatin-resistant OVCAR3 cells and observed the upregulation of Wnt5a-ROR2 in OVCAR3cis, consistent with our previous results showing that Wnt5a-ROR2 expression is linked to cisplatin resistance development in OC models 12 . Furthermore, we observed a significant increase in ROR1 protein expression following DEX treatment in OC cells, and this correlated with the upregulation of ROR1 downstream signaling such as RhoA, YAP/TAZ, and BMI-1 levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we tested the effect of the glucocorticoid DEX on ROR1 signaling activation and analyzed the global changes in drug responses in OC preclinical models, including platinum-resistant cells. We developed cisplatin-resistant OVCAR3 cells and observed the upregulation of Wnt5a-ROR2 in OVCAR3cis, consistent with our previous results showing that Wnt5a-ROR2 expression is linked to cisplatin resistance development in OC models 12 . Furthermore, we observed a significant increase in ROR1 protein expression following DEX treatment in OC cells, and this correlated with the upregulation of ROR1 downstream signaling such as RhoA, YAP/TAZ, and BMI-1 levels.…”
Section: Discussionsupporting
confidence: 90%
“…The ROR family of proteins belongs to the non-canonical Wnt pathway and is comprised of two receptors, ROR1 and ROR2 that can bind Wnt5a ligand via their extracellular domain 10 . In OC, both ROR1 and ROR2 are important for cell growth, migration, and invasion 11 , while high levels of ROR2 correlated with the development of platinum resistance 12 . Furthermore, ROR1-positive OC cells have stemness properties, as demonstrated by high levels of ALDH1 or cell surface expression of cancer stem cell (CSC) markers such as CD133 and CD44 13 .…”
Section: Introductionmentioning
confidence: 99%
“…a, b Western blot analysis of the expression of osteogenic specific markers after osteogenic induction for 3 weeks. n = 3, *P < 0.05 vs. mBMSC-mock1; $ P < 0.05 vs. mBMSC-mock2; # P < 0.05 vs. mBMSC-sh-Ror2 contained a GAS motif, which is speculated as a cis element for Stats [29,42]. Inhibition of Stat3 in hADSCs reduced the ability of IL-6 to induce Ror2 mRNA expression and osteoblast-like differentiation and calcification [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mice with selective disruption of Stat3 in osteoblasts or osteocytes showed reduced bone formation [27,28]. High level of Ror2 expression in platinumresistant ovarian tumor was found to be coupled with upregulation of Stat3, suggesting that Stat3 might act as the signaling downstream of Ror2 [29]. IL-6 induced the transcription of Ror2 to accelerate osteoblast-like differentiation and calcification in human adipose tissuederived mesenchymal stem cell (hADSCs), while suppression of Stat3 in hADSCs inhibited IL-6-mediated Ror2 expression and mineralization [30].…”
Section: Introductionmentioning
confidence: 99%
“…Next to the established function of the RORs in cell proliferation, another detrimental consequence of active WNT/ROR signaling in cancer has currently emerged, namely the establishment of resistant tumor cell clones. Several studies have reported the upregulation of ROR1 or ROR2 in chemoresistant cancer cell lines [ 88 , 99 ] as well as in patient-derived tissues after chemo- or targeted therapy [ 100 , 101 , 102 ]. In melanoma, O’Connell et al initially observed opposing roles for ROR1 and ROR2: melanoma cell lines resistant to inhibition of the serine/threonine-protein kinase B-raf (BRAF) were characterized by upregulated ROR2, but downregulated ROR1 [ 103 ].…”
Section: The Function Of Ror1/2 In Cancermentioning
confidence: 99%